Star Wars : The Rise and Fall of Darth Vader - Windham, Ryder (New York Scholastic Inc., 2007)
Based on all six of the Star Wars movies, tells the story of Anakin Skywalker from his birth in slavery to his death as the powerful Darth Vader.
Keywords: Space warfare -- Good and evil -- Life on other planets